CONSIDERATION OF THE SPECIFICS OF UNDERSTANDING TEXTUAL COMMUNIQU´ES IN DESIGNING DIALOGUES WITH A USER OF AN INFORMATION SYSTEM - Suslow, Walery (Computer Science, 2012)
The paper presents a proposal to take into account the language comprehensionparadigm in an attempt to improve the design methodology of human-computerdialogues. It is assumed that the user treats a system as a subject, i.e. perceivescommunication with the system as a kind of discourse and intuitively treats itas cognition of the world through a fixed image of objective linguistic signs. Dueto the fact that every end-user of a computer system has an individual linguisticcompetence, thesaurus, habits, previous experiences, one can never guaranteethat identical semantic references arise in a variety of audiences. The situationbecomes more stable if one considers the communication aspect of comprehensionon the basis of practice (familiarity of things). It may be expected thata qualified professional user will commit fewer errors, caused by a poor dialogueunderstanding while interacting with the system. Therefore, the main taskof a designer is to speed up and facilitate the learning process, which can beachieved by running the process of constructive rational understanding.